Analysis and Implementation of Computer Networks to Support Learning (Case study: Adiluwih Islamic Vocational High School) - Ricco Herdiyan Saputra; Dede Andriyansyah (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
In the increasingly rapid development of technology, various aspects of work, education, health, and the community environment in the world and Indonesia. In desperate need of various technological developments that are used to support the smoothness and convenience of these various aspects. And one of them is the development of technology in the field of computer networks. To design a network architecture that can be implemented, defining a network architecture that can be arranged and defined, to be able to create a network architecture that has the proper functions and uses and as desired. The method used is the Network Development Life Cycle (NDLC). The researchers analyzed the existing network design at SMK Islam Adiluwih. The results of the analysis and design of the Internet network at SMK Adiluwih are expected to help and meet the needs of teachers and all students in accessing the Internet as desired.